Educação e Património: Memória, Identidade e Dinâmicas Educativas - Morgado, Elsa (2024)
This study aims to develop a critical reflection on the theme under analysis, which invariably relates to the cultural diversity affecting the formation of future generations, their challenges, and opportunities. Theoretical Framework: This work refers to the dichotomous dynamics between education and heritage on a basis of intrinsically dialogic reflection arising from the relational structure between memory and identity and educational dynamics as the epicenter of this same interaction and conceptual deepening. A properly cared for (and lived) cultural heritage provides us with a broad view of the history of a country, a people, or a particular group that, in due time, will actively contribute to the formation of the identity of that country, that people, or group. This cycle determines the formation of groups, social categories, and the recovery of memory, thus triggering a connection between the citizen and their roots. Promoting the preservation, continuity, and informed innovation of current and future interlocutors. Science, technology, and innovation play a preponderant role at various levels and domains of this dialogical matrix between identity, heritage, and cultural dimensions and the educational dimension of commitment to the formation of contemporary and future generations, grounded in an educational perspective aimed at the transformative action of man (and his activity) in the world in which he is inserted and that surrounds him. Method: Narrative literature review, aiming to describe or discuss the current state of the researched topic. Results and Discussion: It is inferred that the relationship between education and heritage is intrinsic, as both are linked to the preservation of the memory and cultural identity of a society. Heritage, whether material or immaterial, is a rich source of knowledge that can be explored in educational contexts to promote understanding of the history and traditions of a people. Research Implications: Certain considerations for reflection and improvement are envisaged for the future, based on the structure and conceptual basis emanating from the authors (and works) of reference that deal with the theme under discussion and reflection. Originality/Value: This review triangulates, in an original way, the relationship between memory, identity, and educational dynamics in the context of education and heritage. Promoting, on the one hand, reflection on the theme and the articulation between areas and, on the other hand, challenging new studies to put into interaction the intersection of knowledge from conceptually close areas in teaching/investigative professional activity.